Multi-Stripe Seismic Assessment of Precast Industrial Buildings With Cladding Panels - Gajera, Krunal; Dal Lago, Bruno; Capacci, Luca; Biondini, Fabio (Frontiers in Built Environment, 2021)
Following the empirical observation of widespread collapses of cladding panel connections of precast industrial buildings under recent seismic events, new design solutions have been developed in the framework of the European project SAFECLADDING, including isostatic systems effectively decoupling the seismic response of frame structure and cladding panels. The present paper is aimed at evaluating the seismic response and vulnerability of precast frame structures employing pendulum, cantilever, and rocking cladding connection systems. Within the framework of the research project RINTC–Implicit seismic risk of code-conforming structures funded by the Italian Civil Protection Department within the ReLUIS program, the seismic performance of a typical precast industrial building has been assessed with a probabilistic approach based on the results of static and multi-stripe dynamic non-linear analyses. The seismic vulnerability assessment of each structural system has been carried out with reference to life safety and damage limit states considering three sites of increasing seismic hazard in Italy. The effect of distributed panel mass modeling vs. more common lumped mass modeling has been analyzed and critically commented based on the results of demand over capacity (D/C) ratios. Moreover, biaxial seismic D/C ratios have been evaluated for realistic strong hinge connections for cladding panels.